Powershift : transform any situation, close any deal, and achieve any outcome - John, Daymond, 1969-; Paisner, Daniel (Currency, 2020)
"Bestselling author and star of ABC's Shark Tank Daymond John reveals how to drive the change you want to see in your life by mastering the three prongs of influence: reputation, negotiation, and relationships. Have you ever wanted to make a big change in your life but wasn't sure where to start? In Powershift, bestselling author, Founder & CEO of FUBU, and star of ABC's Shark Tank Daymond John shares the answer. To drive the change you want to see in your life, you'd better have your foot on the gas pedal and be ready to switch gears. But first, you need to lay out the groundwork so you're prepared to seize every opportunity you're given: by establishing reputation and creating a sphere of influence, by learning how to negotiate for yourself and your position, and by working to maintain those essential relationships so you can call on them later on. Drawing on never-before-told stories from his life and career, Daymond shares the lessons and principles that got him to where he is today: from how he remade his public image as he made the unlikely transition from clothing mogul to television personality, to new negotiation strategies he honed "in the tank," to how he learned to navigate a new web of relationships as a serial entrepreneur. Whether you're an innovator working to turn your big idea into a reality, a seasoned professional looking to land a major promotion, or a busy parent trying to find more time to focus on your health and well-being, Daymond shows you how to shift your power and energy in a new direction and achieve the change - big or small - that you've been dreaming of"--